Curating Complex, Dynamic and Distributed Data: Telehealth as a Laboratory for Strategy - Jenny Ure; Tasneem Irshad; Janet Hanley; Angus Whyte; Claudia Pagliari; Hilary Pinnock; Brian McKinstry (International Journal of Digital Curation, 2011)
Telehealth monitoring data is now being collected across large populations of patients with chronic diseases such as stroke, hypertension, COPD and dementia. These large, complex and heterogeneous datasets, including distributed sensor and mobile datasets, present real opportunities for knowledge discovery and re-use, however they also generate new challenges for curation. This paper uses qualitative research with stakeholders in two nationally-funded telehealth projects to outline the perceptions, practices and preferences of different stakeholders with regard to data curation. Telehealth provides a living laboratory for the very different challenges implicit in designing and managing data infrastructure for embedded and ubiquitous computing. Here, technical and human agents are distributed, and interaction and state change is a central component of design, rather than an inconvenient challenge to it. The authors argue that there are lessons to be learned from other domains where data infrastructure has been radically rethought to address these challenges.